From panegyrics to tv soaps a critical study of the representation of mappilapattu and oppana in popular culture cinema and television - Shibila, A (Government Victoria College Palakkad, University of Calicut, 2025)
This thesis examines the representation of the traditional Mappila folk art forms-Mappilapattu and Oppana- in the realms of popular culture, particularly through cinema andtelevision. Folk art, once deeply embedded in community life and collective rituals, is nowincreasingly mediated through mass media. Drawing from popular culture theory, folklorestudies, gaze theory, and insights from globalisation studies, the research analyses how thesecultural expressions are reimagined and reinterpreted when circulated as popular art. Throughtextual and content analysis of selected film songs and clips of TV soaps, the researchuncovers how popular culture functions both as a site of resistance and commodification.The first chapter outlines the historical and social formation of the Mappilacommunity, establishing the context of Mappilapattu and Oppana. The second chapter,drawing from folklore theory, explores these art forms in their communal dimensions. Thethird chapter analyses how they are reinterpreted in selected Malayalam cinema. The fourthchapter examines reality TV, employing glocalisation theory to understand how globalentertainment formats adapt traditional practices. The findings reveal a shift from communalperformance to mediated entertainment, where art forms are selectively stylised orstandardised for broader appeal. However, these same media spaces also allow for partialagency and reinterpretation by folk artists. The study concludes that the representation of folkart in popular culture is a negotiated space where preservation, adaptation, andcommodification occur simultaneously.
Keywords: Popular Culture; Mappilapattu; Oppana; Folk Art; Popular Art; Mass Art